Cervical Lymphadenopathy Mimicking Angioimmunoblastic T-Cell Lymphoma after Dapsone-Induced Hypersensitivity Syndrome - Rim, Min Young (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2012)
A 36-year-old woman presented with erythematous confluent macules on her whole body with fever and chills associated with jaundice after 8 months of dapsone therapy. Her symptoms had developed progressively, and a physical examination revealed bilateral cervical lymphadenopathy and splenomegaly. Excisional biopsy of a cervical lymph node showed effacement of the normal architecture with atypical lymphoid hyperplasia and proliferation of high endothelial venules compatible with angioimmunoblastic T-cell lymphoma. However, it was assumed that the cervical lymphadenopathy was a clinical manifestation of a systemic hypersensitivity reaction because her clinical course was reminiscent of dapsone-induced hypersensitivity syndrome. A liver biopsy revealed drug-induced hepatitis with no evidence of lymphomatous involvement. Intravenous glucocorticoid was immediately initiated and her symptoms and clinical disease dramatically improved. The authors present an unusual case of cervical lymphadenopathy mimicking angioimmunoblastic T-cell lymphoma as an adverse reaction to dapsone.